Applications of event-related potentials in Alzheimer’s disease: a systematic review and analysis - Qian Liang; Zhilin Chen; Xiaohui Tang; Xijin Wang (Frontiers in Aging Neuroscience)
The prevalence of Alzheimer’s disease (AD) has been increasing continuously, representing a major issue for public welfare. Detecting cognitive impairment due to AD at its early stages is an urgent prerequisite for therapeutic treatment to slow or halt disease progression before major brain damage occurs. Event-related potentials (ERPs) are a noninvasive neurophysiological technique with the advantages of objectivity, ease of operation, and real-time reflection of cognitive processing in the brain. The purpose of this paper is to comprehensively assess the application value of ERP in AD. By systematically searching relevant literature in PubMed, Web of Science and Scopus databases, and merging and analyzing the literature included in the study, we explored the roles of various components of ERP in the diagnosis, disease monitoring and pathological mechanism research of AD, and provided a comprehensive overview of the current status and prospect of the application of ERP in AD.